An Integrative Model of Financial Inclusion and Digital Literacy in Promoting Sustainable Economic Growth - Darnilawati, Darnilawati (Nomico, 2026)
Sustainable economic growth has become a central issue in development policy, particularly in developing countries that face challenges related to poverty, inequality, and limited access to financial services. Financial inclusion and digital literacy have increasingly been recognized as key drivers in supporting inclusive and sustainable economic systems. However, previous studies often examine these two factors separately, resulting in limited understanding of their integrated role in promoting sustainable development. Therefore, this study aims to analyze the relationship between financial inclusion and digital literacy and to formulate an integrative conceptual model that explains how these variables jointly contribute to sustainable economic growth. This research employs a qualitative approach using a systematic literature review method. Data were collected from peer-reviewed journal articles indexed in reputable academic databases published between 2021 and 2025, focusing on studies related to financial inclusion, digital literacy, and sustainable development. The data were analyzed using thematic and conceptual synthesis to identify patterns and theoretical linkages among the key variables. The findings indicate that financial inclusion expands access to financial services and promotes MSME development, while digital literacy enhances individuals’ ability to adopt and effectively utilize digital financial technologies. The integration of these two factors contributes to poverty reduction, economic participation, and environmentally sustainable investment. In conclusion, sustainable economic growth can be strengthened through an integrative framework that combines financial inclusion, digital literacy development, supportive ICT infrastructure, and inclusive regulatory policies.